Numerical modelling of oil containment process under current and waves - Xing, Jingru; Chen, Songgui; Stagonas, Dimitris; Yang, Liang (Elsevier, 2023)
This study presents a novel three-phase Fluid–Structure Interaction (FSI) model for simulating the containment of oil spills. The model uses Level Sets to capture the evolution of multiple interfaces and incorporates spring forces on the structure under hybrid wave–current boundary conditions. The implementation of spring forces has been validated through simple harmonic motion models and a wedge falling simulation demonstrates the model’s ability to handle multi-phase deformation. The study compares numerical results with experimental data to study the response of oil spills to wave–current hybrid conditions. Our simulations reveal that when the current exceeds 0.2 m/s, the movement of the boom is dominated by the current and not by the waves or their inertia, providing important information for the design of effective oil spill containment systems.
Keywords: Multi-phase level sets; One-fluid formulation; Fluid–structure interaction (FSI); Numerical tank; Spring mooring